Traumatic impaction of foreign body in the mucobuccal fold of lower anterior region in the oral cavity: A chance finding - Ramya Vinayagam; Bagavad Gita; Sajja Chandrasekaran; Afreena Imami Nazer (Wolters Kluwer Medknow Publications, 2015)
Foreign bodies may be ingested, inserted or deposited in the oral cavity. Iatrogenic foreign bodies such as impression material, amalgam, broken instruments, needles etc., are commonly encountered. These foreign bodies are generally symptomatic and show signs of inflammation pain and purulent discharge. An unusual case of asymptomatic traumatic foreign body (stone) impacted in the lower anterior region due to an accident 3 years back, which was diagnosed during routine oral examination is reported.